Plasma membrane profiling defines an expanded class of cell surface proteins selectively targeted for degradation by HCMV US2 in cooperation with UL141 - Hsu, Jye-Lin; van den Boomen, Dick J H; Tomasec, Peter; Weekes, Michael P; Antrobus, Robin; Stanton, Richard J; Ruckova, Eva; Sugrue, Daniel; Wilkie, Gavin S; Davison, Andrew J; Wilkinson, Gavin W G; Lehner, Paul J (PLOS pathogens, 2015)
Human cytomegalovirus (HCMV) US2, US3, US6 and US11 act in concert to prevent immune recognition of virally infected cells by CD8+ T-lymphocytes through downregulation of MHC class I molecules (MHC-I). Here we show that US2 function goes far beyond MHC-I degradation. A systematic proteomic study using Plasma Membrane Profiling revealed US2 was unique in downregulating additional cellular targets, including: five distinct integrin α-chains, CD112, the interleukin-12 receptor, PTPRJ and thrombomodulin. US2 recruited the cellular E3 ligase TRC8 to direct the proteasomal degradation of all its targets, reminiscent of its degradation of MHC-I. Whereas integrin α-chains were selectively degraded, their integrin β1 binding partner accumulated in the ER. Consequently integrin signaling, cell adhesion and migration were strongly suppressed. US2 was necessary and sufficient for degradation of the majority of its substrates, but remarkably, the HCMV NK cell evasion function UL141 requisitioned US2 to enhance downregulation of the NK cell ligand CD112. UL141 retained CD112 in the ER from where US2 promoted its TRC8-dependent retrotranslocation and degradation. These findings redefine US2 as a multifunctional degradation hub which, through recruitment of the cellular E3 ligase TRC8, modulates diverse immune pathways involved in antigen presentation, NK cell activation, migration and coagulation; and highlight US2's impact on HCMV pathogenesis.
Keywords: Cytomegalovirus; buňky NK; Flow Cytometry; membránové glykoproteiny; nádorové buněčné linie; imunoprecipitace; aktivace lymfocytů; Cell Line, Tumor; Cell Membrane; lidé; Immunoprecipitation; hmotnostní spektrometrie; Killer Cells, Natural; virové proteiny; Humans; Lymphocyte Activation; Immunoblotting; Mass Spectrometry; proteomika; transdukce genetická; průtoková cytometrie; proteiny virového obalu; Viral Proteins; Immune Evasion; Membrane Glycoproteins; vysokoúčinná kapalinová chromatografie; RNA, Small Interfering; malá interferující RNA; Viral Envelope Proteins; Membrane Proteins; membránové proteiny; buněčná membrána; imunitní únik; imunoblotting; Transduction, Genetic; Chromatography, High Pressure Liquid; Proteomics